SUBJECTS OF PHRASES IN ENGLISH LANGUAGE (Journal of the College of Basic Education, 2023)
An English sentence consists of two main parts – namely, the subject and the predicate1 · The subject is a noun phrase (NP) which can be realized by a noun, a pronoun, a word or a group of words. The predicate, on the other hand, is the verb phrase of the sentence. It consists of , beside the verb- the central element in sentence, all the auxiliaries, modifiers, etc. (Zandvoort, 1972: 196; Lapalombara, 1976: 32).